Design and performance evaluation of bitwise retransmission schemes in wireless sensor networks - Pavel Loskot (Physical Communication, 2019)
The previously proposed bitwise retransmission schemes which retransmit only selected bits to accumulate their reliability are designed and evaluated. Unlike conventional automatic repeat request (ARQ) schemes, the bitwise retransmission schemes do not require a checksum for error detection. The bitwise retransmission decisions and combining can be performed either after demodulation of the received symbols or after channel decoding. The design and analysis assume error-free feedback, however, the impact of feedback errors is also considered. The bit-error rate (BER) expressions are derived and verified by computer simulations in order to optimize the parameters of the retransmission schemes. The BER performance of coded and uncoded bitwise retransmissions is compared with a hybrid ARQ (HARQ) scheme over additive white Gaussian noise (AWGN), slow fading, and fast fading channels. It is shown that bitwise retransmissions outperform block repetition coding (BRC) over AWGN channels. In addition, the selection diversity created by the bitwise retransmissions can outperform the HARQ at large signal-to-noise ratio (SNR) over fast fading channels. Finally, the practical design of a bitwise retransmission protocol for data fusion in wireless sensor networks is presented assuming Zigbee, WiFi and Bluetooth system parameters.